2018
DOI: 10.1097/coc.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Trastuzumab and Anthracycline-induced Cardiotoxicity Using Angiotensin-converting Enzyme Inhibitors or β-blockers in Older Adults With Breast Cancer

Abstract: ACEIs/BBs show favorable effects on preventing cardiotoxicity and improving survival in female breast cancer patients undergoing trastuzumab/anthracycline treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 47 publications
0
23
1
2
Order By: Relevance
“…The adjusted hazard ratio for cardiotoxicity and allcause mortality was 0.77 (95% CI, 0.62 to 0.95) in the ACEI group and 0.79 (95% CI, 0.70 to 0.90) in the BB group, compared to the hazards in the non-exposed (to either ACEI or BB) group. Starting ACEIs/BBs ≤6 months after the initiation of trastuzumab/anthracyclines and having exposed duration of ≥6 months were associated with decreased risk of cardiotoxicity and allcause mortality [98]. Although suggesting a clinical benefit, the results are from an observational study and cannot be attributed to specific medications or drug classes or to primary, secondary, or tertiary prevention.…”
Section: Clinical Studies In Adultsmentioning
confidence: 81%
“…The adjusted hazard ratio for cardiotoxicity and allcause mortality was 0.77 (95% CI, 0.62 to 0.95) in the ACEI group and 0.79 (95% CI, 0.70 to 0.90) in the BB group, compared to the hazards in the non-exposed (to either ACEI or BB) group. Starting ACEIs/BBs ≤6 months after the initiation of trastuzumab/anthracyclines and having exposed duration of ≥6 months were associated with decreased risk of cardiotoxicity and allcause mortality [98]. Although suggesting a clinical benefit, the results are from an observational study and cannot be attributed to specific medications or drug classes or to primary, secondary, or tertiary prevention.…”
Section: Clinical Studies In Adultsmentioning
confidence: 81%
“…One of the new generation BBs and a most commonly used agent, carvedilol, showed strong antioxidant characteristics and greater protective effect on anthracycline-induced cardiomyopathy ( 6 , 8 ). A recent report demonstrated that favorable effects of ACE inhibitors and BBs on preventing cardiotoxicity and improving survival of breast cancer patients treated with trastuzumab and/or anthracyclines ( 65 ). Moreover, beta-adrenergic blockade with nebivolol, metoprolol, lisinopril, etc., has also been proven to be effective for cardiomyopathy ( 66 , 67 ).…”
Section: Prevention Of Cardiotoxicity and Future Directionsmentioning
confidence: 99%
“…This gap in knowledge of how to manage a large proportion of pediatric cancer patients needs to be addressed. For example, while multiple clinical trials in adults have reported a benefit with ACE inhibitors [17], there are very few pediatric trials in cancer patients with mixed results. A recent trial that randomized 84 pediatric patients with leukemia to receive 6 months of ACE inhibitor did not show a difference in left ventricular systolic dysfunction between treatment and placebo groups; however, fewer patients in the treatment group showed an increase in pro-brain natriuretic peptide compared to the placebo group [18].…”
Section: Developing Standardized Practicementioning
confidence: 99%